Appropriation and educational uses of cell phones by students and university teachers - Javier Organista Sandoval; Arturo Serrano-Santoyo; Lewis McAnally Salas; Gilles Lavigne (Universidad Autónoma de Baja California, 2013)
Abstract This article presents a study on appropriation and educational uses of cell phones. For the research, a random sample of 954 students and 246 teachers was selected, representing respectively 12% and 24% of the total population in two facilities of UABC in Ensenada, Mexico. Our survey showed that 97% of teachers or students have some kind of cell phone or smartphone. However, we observed that one of every four interactions with the mobile device had a concrete educational purpose. We also found that in general the educational use of the cell phone is mainly aimed to establish communication between the students and to access information via Internet. However, in spite of its limitations, our results show that the cell phone is a technological tool with great pedagogical potential. We suggest that institutional policies are necessary in order to tap that the cell phone potential to adequately support the teaching-learning process.